2020
DOI: 10.1155/2020/7680508
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Gas Sensing Behavior of Hybridization between Reduced Graphene Oxide and Gold Nanoparticles

Abstract: Stack and composite are the two ways of hybridization between gold nanoparticles (AuNPs) and reduced graphene oxide (rGO) which have been fabricated and tested the ability to detect NH3 gas at room temperature. The device based on the rGO-AuNP composite structure exhibited the highest response and the fastest response and recovery time compared to stack and bare rGO. The red shift of a resonant peak in the absorption spectra and the negative shift in the binding energy of 4f5/2 peak indicated that the remarkab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Consequently, the gas-sensing properties of rGO should be strongly dependent on the reduction process and the remaining oxygenated groups on its surface. Some recent strategies to tailor and improve these materials' performance as gassensitive layers are based on combining rGO with other nanostructured materials such as metal nanoparticles [29,30], quantum dots [31,32], transition metal dichalcogenides [33][34][35][36], and semiconducting metal oxides (SMOx) nanoparticles [37]. Recent work on nanocomposites based on rGO-SMOx demonstrated that these materials should achieve highperformance at a low-temperature range (<150 • C).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the gas-sensing properties of rGO should be strongly dependent on the reduction process and the remaining oxygenated groups on its surface. Some recent strategies to tailor and improve these materials' performance as gassensitive layers are based on combining rGO with other nanostructured materials such as metal nanoparticles [29,30], quantum dots [31,32], transition metal dichalcogenides [33][34][35][36], and semiconducting metal oxides (SMOx) nanoparticles [37]. Recent work on nanocomposites based on rGO-SMOx demonstrated that these materials should achieve highperformance at a low-temperature range (<150 • C).…”
Section: Introductionmentioning
confidence: 99%